CORRELATION BETWEEN TOLERANCE TOWARDS UNCERTAINTY AND THE PERSON'S ADAPTIVE READINESS FOR CHANGE - R M Shamionov (Peoples' Friendship University of Russia (RUDN University), 2016)
The paper presents a theoretical and empirical analysis of how tolerance towards uncertainty correlates with the individual's adaptive readiness. Adaptive readiness is defined as an integral concept that includes not only the person's notions about his/her own ability to adapt (in general or to a particular (specific) situation), but also the affirmations about his/her ability to cope with difficulties arising in the process of the interaction with other people; changes in the economic, environmental, political, and other spheres of life; his/her health or his/her socio-psychological or other status, etc.. Studies prove that adaptive readiness (affirmation), adaptiveness (personality property), and readiness for change (attitude) are predictors of tolerance towards uncertainty. It is shown that, when a variable is singularly and conjointly introduced into the regression equation, adaptive readiness influences the parameters of tolerance in the most profound way relative to both socio-psychological adaptiveness and the parameters of readiness for change.